Evaluation of Teaching Attendance in Implementation of Distance Learning in English Lessons during Covid-19 at Muhammadiyah Serui - Harianto Harianto; Amaluddin Amaluddin; Rafiah Nur (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Distance learning with an online format is one of the channels that are widely practiced by educational institutions during the COVID-19 pandemic. Inevitably, the practice of distance education has attracted the attention of many researchers to examine it from various perspectives, considering that the change in the format of learning from face-to-face to distance learning occurs rapidly and massively affects all educational institutions around the world, including them. Indonesia. This rapid change in learning formats presents both challenges and opportunities in integrating technology with distance formats. This study investigates the online teaching practice of English teachers in presenting English lessons at SMP Muhammadiyah Serui during the COVID-19 pandemic. This study uses the lens of the teaching attendance framework to analyze online teaching practices, considering that a strong teaching presence element is needed in learning that only relies on written language in online learning. This study uses a qualitative design. The data set, consisting of transcripts of online discussion posts and interviews with an English teacher, principal, and 13 deliberately selected students, was analyzed deductively. The findings of this study are that English teachers have not presented teaching attendance based on indicators in the three components of teaching attendance, including the categories of design & organization, facilitation discourse, and direct teaching.